Plant Monitoring with Artificial Intelligence Chatbot - Ahmad Fadzil, Muhammad Haziq; Ab Kadir, Diyana (Journal of Computing Technologies and Creative Content, 2020)
This paper is about an IoT system with AI chatting bot for plant monitoring which can monitor the level of soil moisture, light, temperature and fertility of our plant anywhere and anytime. As we know, plant is a living nature that really close to our life thanks to their beauty and the benefits that they provide to us and to the surrounding as well. People like to grow their favorite plants. Some of them even setup a small garden in their house to make their house restful and calm. However somehow they do not have enough time to watch after their plant. They simply water the plant once a day without even knowing what the plant actually needs. In this project, we implement a chatting bot to help us update the status of the plant while we were outside the house. The chatting bot will inform the owner about the current condition of the plant and its current need. In addition, the project collects and records the soil moisture, temperature, light of the surrounding, and also the plant’s fertility. By monitoring these environmental variables continuously, it gives us an information of which factor affects growth of the plant. User can analyze the graph and determine the cause of the plant getting withered or the leaves getting dry and brown. Keywords—Raspberry Pi, Artificial Intelligence, IoT, Plant Monitoring.